2020
DOI: 10.1515/jirspa-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

PETTLEP imagery and tennis service performance: an applied investigation

Abstract: Tennis is one of the most popular and widely played sports enjoyed by players of different age groups and genders as a profession as well as a mode of recreation. A novel method, PETTLEP imagery combines both conventional and non-conventional style of training of an athlete and improves one’s performance. This study aimed to analyze the tennis service performance of junior tennis players based on PETTLEP imagery training. Forty-four junior male tennis players (Mage=13.22 years, SD=0.42) were selected for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
(66 reference statements)
2
11
0
2
Order By: Relevance
“…As hypothesized, the results of the study first show that the participants in the MI groups, who performed motor imagery before the actual practice of the service, had a higher percentage of successful performances than the participants in the Control group, who had no instructions other than those concerning the steps to be taken for the serve. These results are consistent with those of previous studies that have shown the beneficial effects of using MI interventions in experienced (e.g., Dominique et al, in press;Cherappurath et al, 2020), nonexpert (e.g., Atienza et al, 1998;Dana & Gozalzadeh, 2017;Fekih et al, 2020;Guillot et al, 2012) and novice (e.g., Féry et al, 2000;Noel, 1980) tennis players. Moreover, as in the study by Guillot et al (2013), the results of this experiment highlight the positive effects of using an external visual MI practice in combination with physical practice for beginners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As hypothesized, the results of the study first show that the participants in the MI groups, who performed motor imagery before the actual practice of the service, had a higher percentage of successful performances than the participants in the Control group, who had no instructions other than those concerning the steps to be taken for the serve. These results are consistent with those of previous studies that have shown the beneficial effects of using MI interventions in experienced (e.g., Dominique et al, in press;Cherappurath et al, 2020), nonexpert (e.g., Atienza et al, 1998;Dana & Gozalzadeh, 2017;Fekih et al, 2020;Guillot et al, 2012) and novice (e.g., Féry et al, 2000;Noel, 1980) tennis players. Moreover, as in the study by Guillot et al (2013), the results of this experiment highlight the positive effects of using an external visual MI practice in combination with physical practice for beginners.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have supported instructional self-talk as an effective tool for skill acquisition and performance improvement in novice tennis players making volley shots (Cutton & Landin, 2007) or skilled players performing services (Malouff et al, 2008). The latter authors and others have also reported that MI interventions have beneficial effects on tennis movement accuracy and performance (e.g., Cherappurath et al, 2020;Guillot et al, 2013) and that a combination of MI and self-talk can enhance motor performance in a precision task (Cumming et al, 2006). This has therefore been recommended during pre-motor execution in tennis (Morais et al, 2019).…”
Section: Combined With Motor Imagerymentioning
confidence: 99%
“…The present review revealed that MI can be used with tennis players of all skill levels. Indeed, while beneficial effects have been observed in novice players (e.g., Dana & Gozalzadeh, 2017;Féry & Morizot, 2000;Jung et al, 2015), other studies have also shown improvements in performance in intermediate level (e.g., Cherappurath et al, 2020;de Sousa Fortes et al, 2019;Morais et al, 2019) or experts (e.g., Di Corrado et al, 2019;Dominique et al, 2021;Hegazy et al, 2015) tennis players. These results confirm those of previous studies which have shown that MI interventions can be beneficial regardless of the level of practice of the participants (Toth et al, 2020) and can be used by children and pre-teens (Cherappurath et al, 2017;Dereceli, 2019;Di Corrado et al, 2020;Dohm et al, 2019;Guillot et al, 2013) in motor learning context.…”
Section: Imagery and Participantsmentioning
confidence: 99%
“…El diseño de la intervención basado en la práctica imaginada se respaldó en las teorías de bioinformación (Lang, 1979) y equivalencia funcional (Bonnet et al, 1997), además, se ajustó al modelo PETTLEP. Al igual que en este estudio, investigaciones previas (Cherappurath et al, 2020;Post, Wrisberg y Mullins 2010;Smith et al, 2001;Williams et al, 2010) reportaron resultados de efectividad al implementar la práctica imaginada, aunque en otros deportes como hockey o baloncesto, respectivamente. Por otro lado, el modelo PETTLEP se ha puesto a prueba en varias ocasiones (Anuar et al, 2016;Anuar et al, 2017;Marshall y Gibson, 2017) y ha demostrado ser una aproximación efectiva para la mejora de la habilidad de imaginería.…”
Section: Discussionunclassified
“…La práctica imaginada inuye en el rendimiento del individuo de distintas maneras, como en el aprendizaje, o mejora, de habilidades en el deporte (Cherappurath et al, 2020;Pocock, Dicks, elwell, Chapman y Barker, 2019), el aumento de la motivación (Beşiktaş y Biçer, 2013;Chang, 2018), la cohesión de equipo (Adegbesan, 2010;Shearer, 2015), el manejo del estrés (Williams, Cumming y Balanos, 2010), la regulación de la ansiedad (Hale y Whitehouse, 1998; Monsma y Overby, 2004; Williams y Cumming, 2016) y el fortalecimiento de la conanza y la autoecacia (Callow, Hardy y Hall, 2002;Jenny, Munroe-Chandler, Hall y Hall, 2014;Marshall y Gibson, 2017;Munroe-Chandler, Hall y Fishburne, 2008;Rattanakoses et al, 2009). El presente estudio se enfocó en la autoconanza, concepto denido por Vealey (1986; y entendido como la creencia o grado de certeza que los individuos poseen acerca de su habilidad para ser exitosos en el deporte.…”
Section: Introductionunclassified